Stock and bond market interaction: Does momentum spill over? - Gebhardt, William R.; Hvidkjaer, Soeren; Swaminathan, Bhaskaran (Journal of Financial Economics, 2005)
This paper examines the interaction between momentum in the returns of equities and corporate bonds. We find that investment grade corporate bonds do not exhibit momentum at the three- to 12-month horizons. Instead, the evidence suggests that they exhibit reversals. However, significant evidence exists of a momentum spillover from equities to investment grade corporate bonds of the same firm. Firms earning high (low) equity returns over the previous year earn high (low) bond returns the following year. The spillover results are stronger among firms with lower-grade debt and higher equity trading volume, seem robust to various risk and liquidity controls, and hold even after controlling for past earnings surprises. In examining the source of the spillover, we find that the bond ratings of firms with positive (negative) equity momentum continue to improve (deteriorate) in the future, suggesting underreaction to the information in past equity prices about changing default risk is a likely source of the spillover effect. Overall, our results suggest that both equity and debt underreact to firm fundamentals, but past equity returns is a better proxy of firm fundamentals than past bond returns.